الموظف العام دراسة قانونية على ضوء القانون رقم 12 لسنة 2010 (Comprehensive Journal of Science, 2025)
: The aim of studying the public employee as a legal study is to stand on the nature of the public employee according to the legislation in force in the comparative countries and to clarify the rights and duties of the public employee and the extent of their agreement, and to clarify the extent of its impact on society and those dealing with him in the environment in which he lives. The problem addressed by the research is the nature of the employee and how he performs duties and enjoys the stipulated rights, and the extent of the impact of amending legislation on his general situation. The research has a special importance in the employee’s knowledge of his rights and duties and a general importance in that whoever reads the research has an idea about this employee. The aim of the research is to stand on the contemporary legislation that stipulates the public employee and to clarify his importance for society as well as for the regular and steady operation of the public service.
Keywords: Public employee - rights-Duties - Grievance - Legislation.